Diversity and distribution of genus Amegilla Friese, 1897 in Bosnia and Herzegovina (Hymenoptera: Apoidea) (Annals of the Institute of Biology, 2023)
In Bosnia and Herzegovina, the genus Amegilla Friese, 1897 is represented by four species. The known diversity of species of the genus Amegilla in Bosnia and Herzegovina was compared with current data on the diversity of bees in the Balkan Peninsula and Europe as a whole. Through extensive field research carried out in Bosnia and Herzegovina, the presence of the following Amegilla species was established: Amegilla albigena (Lepeletier, 1841), Amegilla garrula (Rossi, 1790), and Amegilla quadrifasciata (de Villers, 1789). Additionally, the species Amegilla magnilabris (Fedtschenko, 1875) was documented based on specimens stored in the Zoological Collection of the National Museum in Bosnia and Herzegovina. The Amegilla species are distributed in the Mediterranean and Pannonian regions. It's significant to mention that the distribution of Amegilla species in Bosnia and Herzegovina appears to be influenced by specific climatic and geographic factors. These species tend to be absent in the Dinaric region characterized by a continental climate, suggesting a preference for other ecological niches. Analyzing the distribution data further reveals the thermophilic nature of Amegilla species, primarily favoring open-type habitats. The research results highlight the significance of certain climatic variables in shaping their habitat suitability. For instance, the variable Bio 9, representing the mean temperature of the quarter with the least rainfall (the driest period), significantly influences the suitability of the habitat for Amegilla albigena (38.0%) and Amegilla quadrifasciata (16.1%). Meanwhile, for Amegilla garrula, the variable Bio 1, representing the mean annual temperature, plays a pivotal role, accounting for 36.2% of its habitat suitability. These findings underscore the importance of understanding the intricate relationships between climatic factors and species distribution, shedding light on the ecological intricacies of Amegilla species in Bosnia and Herzegovina.